Biological and sociocultural determinants of increased blood pressure among women with a history of gestational diabetes mellitus in rural China: a retrospective cohort study. Issue 1 (21st January 2022) - Guo, Jia; Lv, Wencong; Jiang, Shan; Tang, Yujia; Long, Qing; Yang, Jundi; Wiley, James Allen; Parry, Monica
Abstract : Objectives: Gestational diabetes mellitus (GDM) increases the risk of hypertension and cardiovascular events among mothers later in life. This risk has not been well recognised by healthcare professionals in rural China. Our objectives were to (1) describe the proportion of rural women with increased blood pressure and a history of GDM; and (2) explore the biological and sociocultural factors associated with increased blood pressure. Design: A retrospective cohort study using data from a cross-sectional survey. Setting: Data were collected in two county-level hospitals in the central south of China between November 2017 and June 2018. Participants: Postpartum women aged >18 years with a history of GDM (N=397). Methods: Biological and sociocultural variables were examined. We used bivariate analyses to examine the associations between time since delivery and 2-hour postload glucose, and logistic regression to determine the biological and sociocultural factors associated with increased postpartum blood pressure. Results: Approximately 20% (n=78) of women had increased blood pressure, defined as a systolic blood pressure ≥130 mm Hg and/or a diastolic blood pressure ≥85 mm Hg. The biological factors of advanced age, family history of hypertension and abnormal 2-hour postload plasma glucose levels were positively associated with increased blood pressure (p<0.05). General self-efficacy was the only sociocultural factor negatively associated with increased blood pressure (p<0.05). Conclusions: One in five rural Chinese postpartum women with a history of GDM were found to have increased blood pressure. Biological and sociocultural factors were associated with increased postpartum blood pressure; women with lower general self-efficacy were more likely to have increased blood pressure. Disseminating knowledge about the high risk of developing increased blood pressure among women with prior GDM in rural China is indicated. Diabetes prevention programmes could consider adding general self-efficacy promotion strategies in this population.